Доцільність використання природних сорбентів для зняття мутагенності рідких фторорганічних відходів виробництва мономера ФС-141 - Ревега, О.М.; Фітель, Н.М.; Боднар, Л.С.; Козуб, Ю.Б. (Цитология и генетика, 2005)
Проведены исследования относительно изучения суммарных мутагенных эффектов в жидких фторорганических отходах производства мономера ФС-141. Выявлена индукция генных мутаций по типу замены пар оснований и сдвига рамки считывания, а также индукция хромосомных аберраций, в частности делеций и транслокаций. Изучена целесообразность использования естественных сорбентов для снятия мутагенности фторорганических отходов. Наиболее эффективными оказались цеолиты и глаукониты. Study of total mutagenic effects of liquid fluorine-organic waste products of monomer FC-141 manufacture has been carried out. Induction of gene mutations according to the mechanism of pair base replacement and shift of reading frame and induction of chromosomal aberrations, in particular deletions and translocations, has been shown. Expediency of use of natural sorbents for mutageneity removal from fluorine-organic waste products was investigated. Zeolites and glauconites appeared to be the most effective ones.